2019
DOI: 10.1007/s13762-019-02512-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical composition of fly-ash cenospheres on their grains size

Abstract: Cenospheres, which are the by-product of hard coal combustion, are characterized by properties allowing for a broad use of this material. The article presents the results of the chemical composition analysis of the cenospheres obtained from various power plants. It has been exhibited that depending on the place of origin, their chemical composition is similar and comparable to fly ash produced in hard coal combustion. A great majority of analysed cenospheres may be classified similarly as the sialic ashes-slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The authors reported [16][17][18][19][20] that the average grain size of microspheres usually ranges from 5 to 500 µm and the average thickness varies from 2 to 30 µm. As suggested Strzałkowska [21] and Danish [22], the size of the particles depends on their chemical composition. For example, an increase in the SiO 2 content in the chemical composition leads to a decrease in the diameter of microspheres.…”
Section: Introductionmentioning
confidence: 83%
“…The authors reported [16][17][18][19][20] that the average grain size of microspheres usually ranges from 5 to 500 µm and the average thickness varies from 2 to 30 µm. As suggested Strzałkowska [21] and Danish [22], the size of the particles depends on their chemical composition. For example, an increase in the SiO 2 content in the chemical composition leads to a decrease in the diameter of microspheres.…”
Section: Introductionmentioning
confidence: 83%
“…Cenospheres are exclusively found in the Ferrosialic and Sialic groups, with the development of internal gas occurring when the molten ash droplet contains at least 5% iron oxide [44]. However, studies by Goodarzi et al [44] have shown that many cenosphere specimens contain even less iron oxide, contradicting the conclusion that iron is always necessary for cenosphere development [45][46][47][48][49]. Ferrocalsialic cenospheres exhibit magnetic properties, while Sialic cenospheres do not [50].…”
Section: Cenosphere Characterizationmentioning
confidence: 99%
“…CS is a ceramic hollow structure particle formed by pulverized coal combustion at 1,000–1,800°C in thermal power plants to generate electricity (Yadav et al , 2021). The size of the CS ranges from 5 to 500 microns (Strzałkowska and Adamczyk, 2020), and their Wt.% is about 1%–2% in coal fly (Zyrkowski et al , 2016). A spherical wall-shaped CS is mullite-rich (Yadav et al , 2020), a chemically inert particle with several trapped gases.…”
Section: Introductionmentioning
confidence: 99%